A Web-Based Material Quality Monitoring Information System for Manufacturing Quality Assurance Based-On Rapid Application Development Framework - Khairunnisa Nasution; Dendy K Pramudito; Annisa Maulana Majid (SAFE-Network, 2026)
This research investigates the construction of a web-based Material Quality Monitoring Information System for PT MBR using the Rapid Application Development method. This study was undertaken because recording incoming materials, defect monitoring, and supplier assessment are still manual processes using Microsoft Excel, resulting in less efficient performance, time-dependent reporting requirements, and higher risk of data input errors and duplication. This research aims to create a system to perform material quality monitoring activities more efficiently, and that is integrated, rather than single task. Methods of data collection which are considered for our study include observation, interviews, and literature reviews. It encompasses requirements, design analysis, implementation, and testing. The development process is to design the system using the Unified Modelling Language and implemented with Laravel, Bootstrap, Chart.js framework and MySQL DB. The system produced has capabilities for handling incoming material data handling, documentation and managing defect data, material quality monitoring dashboard and defect percentage dashboard by suppliers for defect performance assessment. Further, the system can display material quality information in graphs and reports that can be accessed online in real time for ease of monitoring and decision-making of users. The work outcomes indicate that the system developed demonstrates the system integration in that all the material quality information can be integrated in one structured and easy-to-use web platform accessible more seamlessly to the users. Using the black box test results, all the system functions worked according to user requirement. And as such, it can be used by PT MBR for material quality monitoring and supplier evaluation.